The effectiveness of promotional mix (advertising and sales promotion) in enhancing the customer awareness: “study in Agrobank” / Musa Muhammad @ Harun - Muhammad @ Harun, Musa (Faculty of Business and Management, 2009)
Promotion is used to communicate with customers with respect to product offering. Promotion has a key role in determining profitability and market success and is one of the key is “Four Ps” of the marketing mix. The tools that can be employed in the promotional are advertising, sponsorship, public relations personal selling and etc. This project paper which entitled ‘The Effectiveness of Promotion Tools in Enhancing Customer Awareness: Study in Agrobank” purposely to study the influence of promotion tools used by Agrobank in order to enhance the customer awareness. From the study, the researcher can identify the major problems that faced by Agrobank and searching for effective solution on it matter arises such as their advertisement is not enough to attract consumer, lack of information by consumer towards their product, service that they offer, and also the restructuring of company by using new logo and name, etc. Therefore, the researcher comes out with a few recommendations to the company such as emphasize their promotion activities through internet website, need to provide a permanent staff at helps desk and so on. These recommendations will help the bank enhancing customer awareness among the target market and attract them. This report outlining the introduction, literature review, findings and analysis, conclusions and recommendations based on the journal and observation during the practical trainee at Agrobank Jeli Branch, Kelantan.